The golden years: prolonged youth (Revista Electrónica REDINE, 2017)
Whoever coined the term “The Golden Years” was truly brilliant; it is the age that allows us to see the other side of things—when, standing at the summit of life, we can easily distinguish between those who are truly old because they feel that way, and those who, regardless of the years they have lived, enjoy an extended youth.